INFLUENCE OF PLANT HYDROCOLLOIDS ON THE STABILIZATION OF CHOCOLATE MILK - ΓΕΩΡΓΑΚΗΣ Σ. Α. (Journal of the Hellenic Veterinary Medical Society, 1972)
The stabilizing capacity of samples from plant hydrocolloids on the preparation of chocolate—milk was investigated. From the experimental data it is evident that all samples tested were not absolutely suitable for the preparation of chocolate—milk. In general the Karagenans had much better possibilities of utilization for this purpose than other kinds of plant hydrocolloids and at the same time they appeared to be practically more economical. However we must give emphasis to the fact that between the two sorts of Karagenans tested there are differences regarding the increase of viscosity coefficient as well as the economical aspect.